Complement C3 and anti-testosterone antibody in the 150 kDa Bali cattle (Bos sondaicus/javanicus) subordinate follicular fluid peptide observed using MALDI-TOF/TOF-MS - Roesmanto, Bisono; Dradjat, Adji Santoso; Depamede, Sulaiman Ngongu (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study aimed to elucidate the proteome profile of the 150 kDa protein isolated from the subordinate follicle of Bali cattle (Bos sondaicus/javanicus). Some researchers have revealed several factors in the follicular subordinate with a 150 kDa protein substance, which play important roles in the bovine ovulation. Materials and methods: In the present study, subordinate follicles ( 5 mm in diameter) were collected from 10 female Bali cattle from slaughterhouses in Taliwang, Sumbawa of West Nusa Tenggara Province, Indonesia. The follicular liquid was pooled; fractionated using SDSPAGE 10%, the 150 kDa band was sliced and then analyzed using MALDI-TOF/TOF-MS. Results: Mascot search results significantly revealed the presence of four species of proteins/peptides. Of the four peptides, two were predominant i.e. complement C3 and anti-testosterone antibody, which both were 100% identical to complement C3 and anti-testosterone antibody of Bos Taurus cattle. Conclusion: Complement C3 and anti-testosterone antibody are present in the follicle fluid of Bos sondaicus/javanicus cows. These findings are novel in Bali cattle follicles. http://doi.org/10.5455/javar.2018.e240